2022
DOI: 10.52825/ocp.v1i.75
|View full text |Cite
|
Sign up to set email alerts
|

Combining Wire and Arc Additive Manufacturing and Selective Paste Intrusion for Additively Manu-factured Structural Concrete

Abstract: The Selective Paste Intrusion (SPI) is an additive manufacturing method in which thin layers of aggregates are bond selectively by cement paste only where the structure shall arise. In this way, concrete elements with complex geometries and structures can be produced. To meet the optimum between required layer bonding and sufficient shape accuracy, the rheological properties of the cement paste, i.e., its yield stress and dynamic viscosity, are crucial [1, 2]. The combination of the SPI process and the Wire an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Previous investigations revealed that concrete's rheological properties in the SPI process decline above 60°C, resulting from increased yield stress [9,11]. Maintaining a balance between sufficient penetration depth, layer bonding, and shape accuracy is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations revealed that concrete's rheological properties in the SPI process decline above 60°C, resulting from increased yield stress [9,11]. Maintaining a balance between sufficient penetration depth, layer bonding, and shape accuracy is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…High temperatures during WAAM generate heat transfer into the particle bed, consequently reducing water required for concrete hardening and thereby decreasing its strength. Moreover, elevated temperatures influence the cement slurry viscosity and, thus, the penetration depth of the paste into the particle bed [12,13]. For that reason, the development of tailored aggregate particles is a crucial factor for the hybrid process of SPI and WAAM.…”
Section: Introductionmentioning
confidence: 99%